The Influence of Capital Adequacy Ratio, Non-Performing Loans and BI Rate on Probability with Loan To Deposit Ratio as Moderating Variable - Gea, Fransiskus; Mulyanto, Heru (Growth: Journal Management and Business, 2024)
The purpose of this research is to determine the influence of the Capital Adequacy Ratio, Non-Performing Loan and BI Rate on the Probability with Loan To Deposit Ratio as a Moderating Variable in case studies at Bank Persero for the 2016-2023 period. The population in this research is all Persero Banks (Bank Mandiri, Bank Rakyat Indonesia, Bank Negara Indonesia and Bank Tabungan Negara Indonesia. This research uses secondary data and the data analysis method uses panel data regression analysis. The sample used in this research uses non- probability sampling using saturated sampling techniques, so that the number of samples is as large as the population, namely 4 banking companies. Data analysis uses descriptive tests, classical assumption tests, panel data regression analysis and hypothetical testing using the Eviesw 10 tool. Based on the research results, it shows that the Capital Adequacy Ratio has an effect. significantly on Return On Assets, Non Performing Loans have a significant effect with a negative relationship on Return On Assets and the BI Rate interest rate has no effect on Return On Assets. In moderation, the Loan To Deposit Ratio variable is not able to moderate the Capital Adequacy Rati and Non Performing Loan variables. Return On Assets, LDR variable is able to moderate the relationship between BI Rate and Return On Assets. the coefficient of determination (Adjusted R-Square) is 0.476412 which means the dependent variable, namely ROA, can be explained by the independent variables Capital Adequacy Ratio, Non-Performing Loans and BI Rate of 47.64% while the remaining 52.36% is explained by other variables in outside the research model.